Aplikasi Arus Kas Masuk Dan Keluar Di Primer Koperasi Kartika Gajah Mada III - Ela Nuraela; KM. Syarif Haryana; . Rinawati (STMIK Mardira Indonesia, Bandung, 2014)
Information is one of the very important things in this world. With the information, all the things about the development of technology and so forth can be identified quickly. Therefore, to augment existing information, the demand for the use of a computer using computer networks more and more in demand to serve the various needs of certain information. Just as the incoming cash processing activities dam out. If the cash processing can not be recorded properly, then the supervision of revenue and expenditure can not be known, especially in the use of funds outside the financial administration planning office (windfalls). Usually the use of funds outside the plan are not archived properly and financial expenditure done manually. Therefore, this can sometimes lead to operational project activities are not running as it should, and allow causing harm. System development techniques used in this report is OOSE. Keywords: cash processing; applications; PHP; transactions